EFFECT OF METHANOL EXTRACT OF JATROPHA GOSSYPIFOLIA L. ON HAEMATOLOGICAL PARAMETERS OF JUVENILES OF AFRICAN CATFISH CLARIAS GARIEPINUS (BURCHEL) - I, Usman J; A, Galadima; K, Auta I; Y, Abubakar J; K, Abdullahi D (Journal of the Inland Fisheries Society of India, 2021)
Juveniles of the African cat fish Clarias gariepinus (Burchel) of standard length 16.50 Â± 00.25 cm and weight 14.75 Â± 1.25 g were exposed to methanol extract of Jatropha gossypifolia L. Ten fish were placed in each glass aquaria of nominal concentrations 0.00, 3.00, 4.00, 5.00, 6.00 and 7.00 mgl-1 in three replications for 96 hours to determine the acute toxicity using flow through bioassay. The caudal peduncle was severed and blood was collected from the caudal arteries. Haematological parameters showed that the Red Blood Cell (RBC), Haematocrit (Ht), were significantly lower to the control at P=0.05. There was clear case of Haemodilation or erythrocyte destruction or haemolysis from the treated fish as opposed to control. These observations were also dose dependent. The Total Leukocyte Count (TLC) and Neutrophils increased significantly at P=0.05 in fish treated with methanol extract of J. gossypifolia in concentration dependent pattern. These increases were aimed at improving immunological status of the fish as it combats the effects of extracts. Basophils, eosinophils and monocytes were not seen, largely due to their uncertain nature. The use of Jatropha gossypifolia as a means of mass fish harvest distorts the natural haematological parameter of the fish owing to the poisonous nature of the ichthyotoxins in the plant. This implies that other non target organisms will be negatively affected and biomagnifications through food chain is possible. Key words: Jatropha gossypifolia, Haematological count, leukocyte, haematocrit, body defense, neutrophils